2003
DOI: 10.3168/jds.s0022-0302(03)74036-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transforming Growth Factor-beta (TGF-β) on Mammary Development

Abstract: Mammary growth and development in heifers and cows is regulated by a complex interaction of multiple stimuli, including environmental, nutritional, and endocrine factors. The action of these various stimuli is mediated by a host of growth factors, including transforming growth factor-beta (TGF-β). TGF-β is a potent inhibitor of mammary epithelial cell growth and regulates extracellular matrix composition. TGF-β is expressed during bovine mammary development and its expression is particularly high at times of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…Although staining intensity was not directly quantified in this study, we observed stronger intensity for TGF-β1 and TGF-βR2 in the epithelial compartment than in the stromal compartment. Localization of TGF-βR2 was consistent with previous literature that reported TGF-βR2 staining along the alveolar and ductal epithelium of heifers (Plaut et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although staining intensity was not directly quantified in this study, we observed stronger intensity for TGF-β1 and TGF-βR2 in the epithelial compartment than in the stromal compartment. Localization of TGF-βR2 was consistent with previous literature that reported TGF-βR2 staining along the alveolar and ductal epithelium of heifers (Plaut et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…It is also interesting to speculate that the greater number of fibroblasts observed at 1 WD may be due to increased abundance of TGF-β1 in the intralobular stroma at LL. The TGF-β1 protein in late lactation may be in latent form, which is activated by proteases at dry-off (reviewed by Plaut et al, 2003). Activated TGF-β1 may then stimulate proliferation of fibroblasts during involution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the transforming growth factor (TGF)-β is a well-known cytokine with its effect on cell growth and differentiation. TGF-β has 3 known isoforms in mammals; TGF-β1, TGF-β2, and TGF-β3 [22]. It has been reported that only TGF-β1 and TGF-β2 were detected in bovine milk [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Transforming growth factor-betas (TGF-β) comprise a super-family of proteins that includes TGF-β1, β2, and β3 as well as activins and inhibins (Kingsley, 1994). Transforming growth factor-β1 regulates mammary development, and its expression is greatest during periods of tissue remodeling (for review, see Plaut et al, 2003). The role of TGF-β1 has been studied primarily during mammary development and lactation in rodents, with varying results depending on timing and c s o ra s or i ro ac or-o a ary remodeling during the dry period of dairy cows L. D. De Vries ,* T. Casey , † 1 H. Dover ,* M. J. VandeHaar ,* and K. Plaut † location of expression.…”
Section: Introductionmentioning
confidence: 99%